Dendritic Cells in Subcutaneous and Epicardial Adipose Tissue of Subjects with Type 2 Diabetes, Obesity, and Coronary Artery Disease - Mráz, Miloš; Cinkajzlová, Anna; Kloučková, Jana; Lacinová, Zdeňka; Kratochvílová, Helena; Lipš, Michal; Pořízka, Michal; Kopecký, Petr; Lindner, Jaroslav; Kotulák, Tomáš; Netuka, Ivan; Haluzík, Martin (Mediators of inflammation, 2019)
Dendritic cells (DCs) are professional antigen-presenting cells contributing to regulation of lymphocyte immune response. DCs are divided into two subtypes: CD11c-positive conventional or myeloid (cDCs) and CD123-positive plasmacytoid (pDCs) DCs. The aim of the study was to assess DCs (HLA-DR+ lineage-) and their subtypes by flow cytometry in peripheral blood and subcutaneous (SAT) and epicardial (EAT) adipose tissue in subjects with (T2DM, n = 12) and without (non-T2DM, n = 17) type 2 diabetes mellitus undergoing elective cardiac surgery. Subjects with T2DM had higher fasting glycemia (8.6 ± 0.7 vs. 5.8 ± 0.2 mmol/l, p < 0.001) and glycated hemoglobin (52.0 ± 3.4 vs. 36.9 ± 1.0 mmol/mol, p < 0.001) and tended to have more pronounced inflammation (hsCRP: 9.8 ± 3.1 vs. 5.1 ± 1.9 mg/ml, p = 0.177) compared with subjects without T2DM. T2DM was associated with reduced total DCs in SAT (1.57 ± 0.65 vs. 4.45 ± 1.56% for T2DM vs. non-T2DM, p = 0.041) with a similar, albeit insignificant, trend in EAT (0.996 ± 0.33 vs. 2.46 ± 0.78% for T2DM vs. non-T2DM, p = 0.171). When analyzing DC subsets, no difference in cDCs was seen between any of the studied groups or adipose tissue pools. In contrast, pDCs were increased in both SAT (13.5 ± 2.0 vs. 4.6 ± 1.9% of DC cells, p = 0.005) and EAT (29.1 ± 8.7 vs. 8.4 ± 2.4% of DC, p = 0.045) of T2DM relative to non-T2DM subjects as well as in EAT of the T2DM group compared with corresponding SAT (29.1 ± 8.7 vs. 13.5 ± 2.0% of DC, p = 0.020). Neither obesity nor coronary artery disease (CAD) significantly influenced the number of total, cDC, or pDC in SAT or EAT according to multiple regression analysis. In summary, T2DM decreased the amount of total dendritic cells in subcutaneous adipose tissue and increased plasmacytoid dendritic cells in subcutaneous and even more in epicardial adipose tissue. These findings suggest a potential role of pDCs in the development of T2DM-associated adipose tissue low-grade inflammation.
Keywords: senioři; Subcutaneous Fat; Obesity; nemoci koronárních tepen; podkožní tuk; Middle Aged; mužské pohlaví; Diabetes Mellitus, Type 2; Pericardium; diabetes mellitus 2. typu; Coronary Artery Disease; Dendritic Cells; dendritické buňky; ženské pohlaví; Humans; Adipose Tissue; lidé středního věku; obezita; perikard; Female; Aged; tuková tkáň; lidé; Male